Important Criteria For Industrialized Building Systems From The Prespectives Of Major Project Partcipants - Lim, Jee Gin (2002)
The revolution in the building industry has resulted in many new building systems being introduced. Consequently, the principal project participants are often faced with decision involving the selection of an appropriate building system. Hence, the research presented in the study focuses on the importance of criteria in selecting the most appropriate building system. It also presents a proposed evaluation model that serves as a guideline for professionals in the industry to perform an initial feasibility study on the selection of industrialized building system.Based on the literature search, the relevant criteria were grouped into six categories: Project Objectives Criteria, Project Characteristics Criteria, Project Constraint Criteria, Technical Oriented Criteria, Performance Oriented Criteria, and Resources Oriented Criteria. The importances of these criteria were identified through a mailed questionnaire, which was employed as the research methodology. From the importance or priorities of criteria obtained from the questionnaire survey, the relationship of criteria among principal project participants was a.'1alyzed. It has found that the criteria among Clients, Architects, and Engineers are strongly correlated, except the criteria of Contractor. In addition, it has also been found that the criteria among principal project participants are independent from methods of construction, methods of contracting and types of project. The proposed evaluation model is set up based on the Analytical Hierarchy Procedure, which enables to set up complex problems involving attributes, subattributes, sub-subattributes, and so on, in an orderly, structured manner. Beside organizing the tangible and intangible decision criteria in a systematic manner, it also provides a structured yet relatively simple solution to the decision-making problems related to selection of an appropriate building system for implementation. As a result of the research, there will be documented sources of information for the selection of an appropriate building system. Moreover, the selection of an appropriate building system can be performed in a systematic and effective method.